Microbiology of the food chain. Horizontal method for the determination of Vibrio spp. Detection of potentially enteropathogenic Vibrio parahaemolyticus, Vibrio cholerae and Vibrio vulnificus Part 1, (16th March 2023) - British Standards Institution
No abstract available